2006
DOI: 10.1542/peds.2005-3082
|View full text |Cite
|
Sign up to set email alerts
|

Parental Rules and Monitoring of Children’s Movie Viewing Associated With Children’s Risk for Smoking and Drinking

Abstract: Parental rules and monitoring of children's movie viewing may have a protective influence on children's risk for smoking and drinking, over and above parental monitoring of nonmedia related behaviors. This highlights a potential role for parents in preventing early initiation of tobacco and alcohol use among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 63 publications
(40 reference statements)
3
56
0
5
Order By: Relevance
“…Pediatricians should counsel parents to recognize the importance of the media, exert control over their children's media choices, keep their children's bedrooms free of TVs and Internet connections, and avoid letting their children see PG-13-and R-rated movies that are inappropriate for them. 61,87,88 Pediatricians and parents also need to be aware of the importance of social networking sites and how they work so that they can effectively counsel children and adolescents about them. 89 3.…”
Section: Positive Impactmentioning
confidence: 99%
“…Pediatricians should counsel parents to recognize the importance of the media, exert control over their children's media choices, keep their children's bedrooms free of TVs and Internet connections, and avoid letting their children see PG-13-and R-rated movies that are inappropriate for them. 61,87,88 Pediatricians and parents also need to be aware of the importance of social networking sites and how they work so that they can effectively counsel children and adolescents about them. 89 3.…”
Section: Positive Impactmentioning
confidence: 99%
“…Firstly, it has been demonstrated in multiple prospective studies that adolescents who experience parental restrictions on adult-rated films (eg, BBFC 18 or MPAA R) have less exposure to smoking and drinking in films and lower rates of smoking and drinking themselves. 2,3,9,10,[33][34][35] Furthermore, these associations are independent of the effect of parenting effectiveness as it is usually measured, 9 raising the possibility that motivating and assisting parents to implement media restrictions between late childhood and early adolescence could have a positive impact on early-onset use of multiple Exposure = Duration of AUFs (vs #27 min). Model 1 = age and gender (N = 5163).…”
mentioning
confidence: 99%
“…29, [70][71][72][73][74][75][76][77] According to a new meta-analysis, it may account for nearly half of smoking initiation in young teenagers. 80 In fact, exposure to movie smoking may even trump parents' smoking status as being the key factor in adolescents' initiation of smoking. 73 A prospective study of more than 3500 teenagers revealed that exposure to R-rated movies doubles the risk of smoking, even when controlling for all other known factors.…”
Section: Drugs In Entertainment Media Cigarettesmentioning
confidence: 99%
“…79 Preadolescents whose parents forbid them from seeing R-rated movies are less likely to begin smoking (or drinking). 80 A study of 735 12-to 14-year-olds, with a 2-year follow-up, revealed that exposure to R-rated movies or having a television in the bedroom significantly increased the risk of smoking initiation for white teenagers. 81 The movie effect seems not to be confined to US teenagers but applies also to teenagers from other countries as well.…”
Section: Drugs In Entertainment Media Cigarettesmentioning
confidence: 99%
See 1 more Smart Citation